EDUCATION OF PHYSICAL EDUCATION: THE IMPORTANCE OF HISTORICAL-CRITICAL THEORIES IN THE DEVELOPMENT AND FORMATION OF AUTONOMOUS HUMAN BEINGS (Fiep Bulletin - online, 2017)
The object of study of this article is the teaching of physical education in basic education (ElementarySchool I). It aims to present the implications of the discipline of physical education in human development in light of the theoreticalassumptions of historical-critical pedagogy and historical-cultural psychology. At a time when discussions about the organizationof public school education are becoming more and more present, we defend the teaching of physical education in order todevelop the highest psychic functions in their maximum possibilities. The text presents the body culture of the movement as ageneric human objectification for itself, whose appropriation, as well as the other contents of the school subjects, becomes acondition for the formation of the conceptual thinking of adolescents. It concludes that the emptying of the teaching of scientificcontents, much defended and proposed by current educational policies, contributes to the impoverished and alienateddevelopment of students.
Keywords: School Education. PE. Historical-Cultural Theory